A cohort study of two intravenous treatments for iron deficiency in patients with heart failure (2019)
Background: Iron deficiency (ID) in patients with heart failure (HF) leads to greater morbidity and mortality and its treatment has been associated with significant improvements in quality of life. Since no head-to-head studies are available, there is uncertainty as to which intravenous iron supplement should be used. This study aimed to compare the effect of ferric carboxymaltose (FCM) and iron saccharate (IS) on clinical and biochemical outcomes in patients with HF and ID. Methods: We reviewed electronic health records from a referral centre in Bogotá, Colombia for patients with HF. We selected records with a follow-up of at least 2 years. Primary outcomes were clinically significant changes in EuroQol-5D (EQ-5D), 6-minute-walk test (6MWT), resolution of ID, and direct costs. Results: We obtained data on 119 patients with a median age of 69 years and a median left ventricular ejection fraction (LVEF) of 35%. All patients met criteria for ID, and 58% were treated with FCM. A significant difference in GFR of 11 mL/min/1.72 m2 was found at baseline between groups. Neither bivariate, nor multivariate analyses could identify significant differences between patients receiving FCM and IS for any of the primary outcomes. Direct cost analysis showed that FCM use generates 2.8 times the cost associated with saccharate use. Conclusions: This retrospective cohort study did not identify any significant differences in clinical or biochemical outcomes between HF patients with ID receiving FCM or IS. Direct cost analysis favoured use of IS in this group of patients. © 2019, © 2019 Belgian Society of Cardiology.